Citizen science and invasive alien species: Predicting the detection of the oak processionary moth Thaumetopoea processionea by moth recorders. (April 2017) - Pocock, Michael J.O.; Roy, Helen E.; Fox, Richard; Ellis, Willem N.; Botham, Marc
Abstract: Invasive alien species, including pests and diseases of plants and animals, are a major cause of biodiversity change and may impact upon human well-being and the economy. If new, potentially invasive, taxa arrive then it is most cost-effective to respond as early in their establishment as possible. Information to support this can be gained from volunteers, i.e. via citizen science. However, it is vital to develop ways of quantifying volunteer recorder effort to assess its contribution to the detection of rare events, such as the arrival of invasive alien species. We considered the potential to detect adult oak processionary moths ( Thaumetopoea processionea ) by amateur naturalists recording moths at light traps. We calculated detection rates from the Netherlands, where T. processionea is widely established and poses a risk to tree health and human health, and applied these to the spatial pattern of moth recording effort in the UK. The probability of recording T. processionea in the Netherlands varied across provinces from 0.05–2.4% per species of macro-moth recorded on a list of species (so equalling 1–52% for a list of 30 species). Applying these rates to the pattern of moth recording in the UK: T. processionea could be detected (detection > 0%), if it were present, in 69% and 4.7% of 10 km and 1 km squares, respectively. However, in most squares detection probability is low (< 1% of 1 km squares have annual detection probability of > 10%). Our study provides a means to objectively assess the use of citizen science as a monitoring tool in the detection of rare events, e.g. the arrival of invasive alien species, occurrence of rare species and natural colonisation. Highlights: Outbreaks of Thaumetopoea processionea could be detected by amateur moth recorders. We analysed moth trapping from the Netherlands and applied results to the UK. T. processionea could be detected, if present, but mostly with low probability. This citizen science is valuable for, but insufficient to guarantee, early detection. It is important to quantify recorder effort in citizen science.